Redemption point - Fox, Candice (Fox, Candice. Crimson Lake novel., 2019)
"When former police detective Ted Conkaffey was wrongly accused of abducting Claire Bingley, he hoped the Queensland rain forest town of Crimson Lake would be a good place to disappear. But nowhere is safe from Claire's devastated father. Dale Bingley has a brutal revenge plan all worked out -- and if Ted doesn't help find the real abductor, he'll be its first casualty. Meanwhile, in a dark roadside hovel called the Barking Frog Inn, the bodies of two young bartenders lie on the beer-sodden floor. It's Detective Inspector Pip Sweeney's first homicide investigation -- complicated by the arrival of private detective Amanda Pharrell to "assist" on the case. Amanda's conviction for murder a decade ago has left her with some odd behavioral traits, top-to-toe tats -- and a keen eye for killers. For Ted and Amanda, the hunt for the truth will draw them into a violent dance with evil. Redemption is certainly in the cards -- but it may well cost them their lives" --